1992
DOI: 10.1073/pnas.89.16.7516
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine dimers in DNA initiate systemic immunosuppression in UV-irradiated mice.

Abstract: Exposing the skin of mice to UV radiation interferes with the induction of delayed and contact hypersensitivity immune responses initiated at nonirradiated sites. The identity of the molecular target in the skin for these Immunosuppressive effects of UV radiation remains controversial. To test the hypothesis that DNA is the target for UV-induced systemic immunosuppression, we exposed C3H mice to UV radiation and then used liposomes to deliver a dimer-specific excision repair enzyme into the epidermis in situ. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
329
1
5

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 491 publications
(353 citation statements)
references
References 16 publications
(12 reference statements)
16
329
1
5
Order By: Relevance
“…Exposure to systemic low-dose solarstimulated UV containing 140 mJ/cm 2 UVB generated activated B cells in sDLNs, which were able to inhibit dendritic cells from stimulating T-cell-mediated skin immune reactions. 29 Pioneering work by Kripke et al 19 demonstrated that CPD formation and transferable suppressor cells are responsible for DTH suppression by systemic UVB, which is unlike this study. Notably, our investigation differed in the Ag and source of UV used.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Exposure to systemic low-dose solarstimulated UV containing 140 mJ/cm 2 UVB generated activated B cells in sDLNs, which were able to inhibit dendritic cells from stimulating T-cell-mediated skin immune reactions. 29 Pioneering work by Kripke et al 19 demonstrated that CPD formation and transferable suppressor cells are responsible for DTH suppression by systemic UVB, which is unlike this study. Notably, our investigation differed in the Ag and source of UV used.…”
Section: Discussioncontrasting
confidence: 72%
“…Control mice received 125 ng of empty liposomes. 19 Transfer of Regulatory CD4 ϩ CD25 ϩ T Cells Mice were irradiated with 150 mJ/cm 2 UVB daily for 3 days and immunized with ova 3 days after the last UVB irradiation; 7 days after immunization, the sDLNs (brachial, axillary, and inguinal) were removed. Cells from unirradiated but immunized mice were also harvested.…”
Section: Application Of Biological Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…23,29,32,33,35 Topically applied exogenous DNA repair enzymes can prevent the immune system suppression induced by UVR. 36 UVR also affects cytoplasmic and membrane targets acting as additional photoreceptors for UVR-induced immunosuppression. 33 Trans-urocanic acid (UCA), present in large amounts in the stratum corneum, is an epidermal chromophore that undergoes photoisomerization to its cis-UCA conformation upon UV exposure; cis-UCA, whose receptor is 5-HT 2A , is involved in skin photocarcinogenesis by acting as a mediator of UV-induced immunosuppression.…”
Section: Molecular Targetsmentioning
confidence: 99%
“…UV-induced DNA damage, predominantly in the form of cyclobutane pyrimidine dimers (CPDs) or thymine dimers, has been recognized as an important molecular trigger for the suppression of immune responses (Applegate et al, 1989) and initiation of UV-carcinogenesis (Applegate et al, 1989;Kripke et al, 1992;Yarosh et al, 1992). In turn, accelerated or enhanced removal of UV-induced CPDs through the topical application of the bacterial DNA repair enzyme, T4 endonuclease V, impaired the development of skin tumors in mice exposed to chronic UV radiation .…”
Section: Il-12 Prevents Uv-induced Immunosuppression Through Dna Repamentioning
confidence: 99%